Optimization of laboratory support costs in a multidisciplinary hospital: possible solutions. Emphasis on the medical information system - A. S. Fedorenko; A. T. Burbello; L. B. Gaikova; E. A. Orishak; E. L. Lataria; O. V. Granatovich; M. V. Pokladova; M. A. Korosteleva (Izdatelstvo OKI, 2023)
Relevance. Due to the constant improvement of the technical base for laboratory research, the number of laboratory tests, both necessary for the patient and secondary, is increasing everywhere, which cannot but affect the financial costs of laboratory support for a medical organization. The growth of costs requires the search for various ways to optimize costs. Given the widespread introduction of medical and laboratory information systems, it is necessary to develop algorithms for optimizing laboratory appointments and with their help. Goal. To show possible ways to optimize the costs of laboratory research, including using the integration of a medical information system and a laboratory information system. Results. The article describes the main possibilities for optimizing the costs of laboratory research in a multidisciplinary hospital, the feature of which is the territorial removal of clinical units and laboratories. The main optimization mechanisms are considered - an adequate ratio of centralization of laboratory research and decentralization (conducting analyzes at the patient's treatment site - point of care testing), the creation of "specializations" for clinical diagnostic laboratories, depending on the profile of clinical units and the number of prescribed analyzes by profile. The principle of introduction into the medical information system of control over the appointments of laboratory tests is shown. The economic evaluation of the results of the integration of the medical information system and the laboratory information system was carried out. Conclusion. The joint use of all existing methods of optimizing laboratory service costs will reduce the financial costs of laboratory support while maintaining the quality of medical care.